Training of trainers on textile engineering and textile technology - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2021)
Researchers from the Faculty of Applied Sciences (FSG) were involved in a series of Training of Trainers (ToT) on 'Modernisation of Curriculum of Textile Engineering and Textile Technology in Asian Countries'.